THE INFLUENCE OF MANAGERIAL LEADERSHIP AND NEW PUBLIC MANAGEMENT ON COMMUNITY WELFARE IN KAIMANA REGENCY MEDIATED BY GOOD GOVERNANCE AND LOCAL GOVERNMENT PERFORMANCE - Mairuma, Matias; Kambuaya, Balthasar; Tuhumena, Ruben; Erari, Anita (Transpublika Publisher, 2024)
This study discusses The Influence of Managerial Leadership and New Public Management on Community Welfare in Kaimana Regency Mediated by Good Governance and Local Government Performance. The approach used with two research designs (mixed method), namely: explanatory (quantitative method) and exploratory (qualitative method). The research sample consisted of 241 people. The quantitative data analysis method uses Structural Equation Modeling (SEM) with the help of the Amos program version 24.0 and qualitative analysis uses interactive models. The research results show that: (1) Managerial leadership has a positive and significant effect on good governance. (2) Managerial leadership directly and indirectly through good governance has a positive and significant effect on government performance. (3) Managerial leadership directly and indirectly through government performance has a positive and significant effect on people's welfare, while through good governance it is not significant. (4) New public management has a positive and significant effect on good governance. (5) New public management directly and indirectly through good governance has a positive and significant effect on government performance. (6) New public management directly has a positive and insignificant effect on people's welfare, while indirectly through good governance and government performance it has a positive and significant effect. (7) Good governance has a positive and significant effect on government performance. (8) Good governance directly has a positive and insignificant effect on community welfare, while indirectly through government performance it has a positive and significant effect. (9) Government performance has a positive and significant effect on community welfare.